ROLE OF POLYMORPHISM FOR THE PANE1 GENE IN THE FORMATION OF REPRODUCTIVE INDICES IN PIGS - N. S. Yudin; R. B. Aitnazarov; S. P. Knyazev; V. A. Bekenev; Yu. V. Podoba; A. B. Berdibaeva; M. I. Voevoda (Вавиловский журнал генетики и селекции)
A tradeoff between reproductive success and immunity is observed in wild and laboratory animals owing to limited energy resources of an organism. Therefore, artificial selection of farm animals for reproductive indices may be accompanied by reduced immune response. Formerly, a single-nucleotide polymorphism in the PANE1 gene for a minor histocompatibility antigen was demonstrated to be positively associated with immunological blood indices and negatively associated with birthweight in Landrace pigs (Huang et al., 2010). In the present study, the frequency of the SNP was determined in domestic pigs and wild boars, and its association with reproductive indices in pigs of the Large White breed. Wild boars, domestic Landrace pigs, and Large White pigs did not differ significantly in the frequency of the rare G allele of PANE1: 11,8, 12,2, and 20,0 %, respectively. Carriership of the CG genotype in females reduced the live litter size and weight.